Situation Analysis on the Price Formation Mechanism of New Energy in China. Issue 1 (November 2020) - Mi, Ning; Liu, Dunnan; Qiao, Ning; Wang, Liyang; Li, Qiang; Zhang, Chao; Xu, Xiaofeng; Yin, Guolong
Abstract: With the rapid development of China's economy, the energy shortage is becoming more and more serious. In order to realize the sustainable development of society, Chinese government has strengthened its support for the development of new energy industry. At present, the total installed capacity of new energy in China has reached 37.2%. Compared with the initial period, the scale of new energy industry has been greatly increased. However, the problem of pricing mechanism of new energy benchmarking in China is increasingly prominent, which not only increases the gap of financial subsidies, but also fails to realize the reasonable optimal allocation of resources. For this purpose, according to the current domestic electricity market environment, this article proposes a new energy price formation mechanism which is more conformed to China's national conditions. Firstly, the article summarizes the existing international new energy pricing mechanisms and analyses the countries in which they are applied. Secondly, through the analysis of the problems and challenges of new energy price in China, the formation mechanism of new energy price in this environment is proposed according to the current situation and future development trend of power market construction in China. Finally, the article summarizes the whole text and proposes relevant policy recommendations as a useful reference for the government to promote the construction of electricity market.